Liver regeneration following experimental major hepatectomy with choledochojejunostomy. Issue 11 (27th August 2015) - Takagi, T; Yokoyama, Y; Kokuryo, T; Yamaguchi, J; Nagino, M
Abstract: Background: Surgical treatment for perihilar cholangiocarcinoma frequently involves hepatectomy and extrahepatic bile duct resection with a choledochojejunostomy (CJ). Cholangitis owing to bilioenteric anastomosis is a common complication. The impact of CJ or regurgitating cholangitis on the liver regeneration process after major hepatectomy is unknown. Methods: Rats underwent 70 per cent hepatectomy (Hx group) or hepatectomy with CJ (Hx + CJ group). The intrahepatic inflammatory response, hepatic regeneration rate, and expression of regeneration-associated genes in the liver and blood were compared between these two groups. Results: Levels of hepatobiliary markers in the blood were significantly higher 4 and 7 days after operation in the Hx + CJ group than the Hx group. Intrahepatic expression of inflammation-associated genes, such as interleukin 6 and tumour necrosis factor α, was also significantly higher in the Hx + CJ group on days 4 and 7. A progressive periportal inflammatory response was identified in the Hx + CJ group by histological examination. The hepatic regeneration rate was significantly lower in the Hx + CJ group than in the Hx group on day 2 (mean(s.d.) 14·2(6·3) versus 21·4(2·6) per cent; P = 0·013) and day 4 (32·4(5·3) versus 41·3(4·4) per cent; P = 0·004). Gene expression levels of hepatic regeneration-promoting factors such as hepatocyte growth factor were significantly lower in the Hx + CJ group than the Hx group on day 1. Conclusion: CJ perturbs early liver regeneration after hepatectomy. An excessive inflammatory response in the liver and suppression of liver regeneration-associated factors may play a role. Surgical relevance Patients with perihilar cholangiocarcinoma may need major hepatectomy with extrahepatic bile duct resection and choledochojejunostomy. This carries a substantial risk of postoperative complications including liver failure. A rat model of partial hepatectomy with choledochojejunostomy was established. The molecular mechanisms underlying liver regeneration, and perturbation of this process by duodenobiliary reflux via the choledochojejunostomy, are described. The results give insight into the pathophysiological events following major hepatectomy with extrahepatic bile duct resection and choledochojejunostomy. This may help to develop a treatment strategy to reduce postoperative liver failure. Abstract : Excessive inflammation, suppression of regeneration